La guerra secondo Norbert Elias e Sigmund Freud: una condizione umana. - André Costa (Cambio)
Instead of conceiving civilisation as a destination, both Norbert Elias and Sigmund Freud have questioned the ideals of the civilised individual, revealing its darker aspects, steeped in contradictions and ambivalences. Both thinkers have integrated barbarism within the concept of civilisation, thereby rewriting the destinies of societies. The civilising process is thus interpreted as a combination of progress and regression, construction and destruction, civilisation and barbarism, influenced by both civilising and de-civilising forces. Experiences of violence generate social traumas that are passed down from generation to generation. In this context, the collapse of civilisation emerges as one of the inevitable fates of the civilising process.